2020
DOI: 10.2514/1.j058625
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Stabilization in Supersonic Flow: Effects of Suction Boundaries

Abstract: 385X to initiate your request. See also AIAA Rights and Permissions www. aiaa.org/randp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To dynamically stabilize the detonation in the engine combustor, Cai et al (2016Cai et al ( , 2019Cai et al ( , 2021 employed a cavity as a flame holder to support an NDW in the supersonic incoming flow and used an expansion wall to attenuate the detonation wave downstream; the opposing effects of the cavity and the expansion wall on the propagation of the detonation wave compete and ultimately equilibrate with each other, which facilitates the stabilization of the NDW in the combustor. Moreover, Cai et al (2020) further attempted to control the propagation of an NDW in a straight channel by setting a series of suction slots behind the detonation front; their numerical results suggested that the dynamic stabilization of the detonation wave can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To dynamically stabilize the detonation in the engine combustor, Cai et al (2016Cai et al ( , 2019Cai et al ( , 2021 employed a cavity as a flame holder to support an NDW in the supersonic incoming flow and used an expansion wall to attenuate the detonation wave downstream; the opposing effects of the cavity and the expansion wall on the propagation of the detonation wave compete and ultimately equilibrate with each other, which facilitates the stabilization of the NDW in the combustor. Moreover, Cai et al (2020) further attempted to control the propagation of an NDW in a straight channel by setting a series of suction slots behind the detonation front; their numerical results suggested that the dynamic stabilization of the detonation wave can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cai et al. (2020) further attempted to control the propagation of an NDW in a straight channel by setting a series of suction slots behind the detonation front; their numerical results suggested that the dynamic stabilization of the detonation wave can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is indeed of great guiding significance for the practical application of detonation engines to explore fundamentally the mechanisms of detonation propagation, stabilisation in expanding combustors with non-uniform supersonic flow. In the present work, the mechanism of self-sustaining detonation propagation with layered velocity in expanding channels is investigated using the dynamic adaptive mesh refinement program AMROC (Adaptive Mesh Refinement in Object-Oriented C++), [37][38][39][40] which has been demonstrated in multiple dimensional detonation simulations 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…In turbofan and other turbine engines, separation of the gas flow through the engine can dramatically increase engine losses, reducing its efficiency [3]. Similarly, in supersonic ramjet (scramjet) engines for hypersonic aircraft, control of BL separation may be a necessary requirement to maintain an effective shock train and ensure continual sufficient thrust as its growth can have a substantial effect on performance [4][5][6][7]. The aerospace engineer has two methods at their disposal to combat these dramatic effects: (1) careful design and engineering of the shape and composition of the bounding surfaces (the body) or (2) direct control of the fluid flow [8].…”
Section: Introductionmentioning
confidence: 99%